Mutant plasminogen in hereditary angioedema is bypassing FXII/kallikrein to generate bradykinin - Hintze, Stefan; Möhl, Britta S.; Beyerl, Jessica; Wulff, Karin; Wieser, Andreas; Bork, Konrad; Meinke, Peter (Frontiers in Physiology, 2023)
Hereditary angioedema (HAE) is characterized by recurrent localized edema in various organs, which can be potentially fatal. There are different types of HAE, which include genetic deficiency of C1 inhibitor (C1-INH) and HAE with normal C1-INH (HAEnCI). In HAEnCI patients mutations have been identified in the F12, PLG, KNG1, ANGPT1, MYOF, and HS3ST6 genes. The release of bradykinin from kininogen via the kallikrein-kinin system (KKS) has been shown to be the main mediator in HAE-FXII, but for HAE-PLG there are only first indications how the PLG mutations can result in bradykinin release. Here we identified in a multi-generation HAE-PLG family an additional F12 mutation, resulting in the loss of one F12 allele. There were no differences in the clinical presentation between HAE-PLG patients with and without the additional F12 mutation, thus we concluded that the KKS is bypassed in HAE-PLG. Structural modeling and in vitro assays using purified proteins confirmed to be the PLG mutation c.988A>G; p.K330E to be a gain of function mutation resulting in an increased bradykinin release by direct cleavage of high molecular weight kininogen (HMWK). Thus, we can provide clinical and experimental evidence that mutant plasminogen in HAE-PLG is bypassing FXII/kallikrein to generate bradykinin.